LAW NUMBER 19 YEAR 2008 ON THE CONCERNING STATE SHARIA BONDS (SBSN / SUKUK) LEX SPECIALIST OF LAW NO. 1 OF 2004 ON STATE TREASURY MAQASHID AL-SHARIAH PERSPECTIVE - Fathur, Fathurrahman (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2020)
Law No. 19 of 2008 concerning the State Shariah Bonds is lex of Law No. 1 of 2004 on the state Treasury and use state assets. SBSN is a product of two dimensions, namely SBSN as an investment product, and SBSN as a country and project financing for the Government and the public interest in containing maqashid as-Shari’ah in order to keep religion, soul, mind, wealth, and honor.